SELEKSI PENERIMAAN ASISTEN LABORATORIUM MENGGUNAKAN ALGORITMA AHP PADA AMIK-STIKOM TUNAS BANGSA PEMATANGSIANTAR - Anjar Wanto; Eko Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2018)
AMIK Tunas Bangsa is a growing university in Pematangsiantar. Therefore, there are still many university activities and activities that are constrained by problems. One of them is the problem in the selection of employees by the foundation to occupy the position of Laboratory Assistant. Problems that arise in the selection process of acceptance of laboratory assistant at AMIK Tunas Bangsa Pematangsiantar is the absence of tools that can assist management in determining the appropriate candidate laboratory assistant to be the best. By building a system to support the decision of using AHP Algorithm (Analytical Hierarchy Process) is expected to assist the Foundation in conducting the assessment and can be used as input (Reference) by the Foundation to make decisions in selecting the appropriate laboratory assistant candidate accepted. Selection of laboratory assistant acceptance using Analytical Hierarchy Process (AHP) algorithm can yield the best alternative, with criteria in the form of an interview, written test, practice test, and GPA. So the selection of acceptance of laboratory assistants can run exactly and in accordance with the expected.